EFFECT OF CREDIT RISK, LIQUIDITY RISK, INTEREST RATE RISK AND CAPITAL ON PUBLIC BANKING PROFITABILITY LISTED IN INDONESIA STOCK EXCHANGE (IDX) - Hariemufti, Yasir (International Journal of Public Budgeting, Accounting and Finance, 2019)
The objective of this study is to examine the effect of credit risk, liquidity risk, interest rate risk, and capital on bank profitability in conventional banks listed on the Indonesia stock exchange (IDX) in 2007-2017. This type of research is descriptive and causality using secondary data, namely financial statements. The population in the study is a conventional public bank registered on the Indonesian stock exchange. This research’s sampling technique used purposive sampling. The sample used was 12 banks. The method used in this research is panel data regression method with a significance level of 5% using a random effect model. Hypothesis testing used t test, F test, and coefficient of determination. The results showed that simultaneous credit risk, liquidity risk, interest rate risk, and capital had a significant effect on bank profitability. Partially credit risk has a negative and significant effect on bank profitability. Interest rate risk has a positive and significant effect. While the liquidity risk and capital variables do not affect bank profitability.